2013
DOI: 10.1007/s10461-013-0473-5
|View full text |Cite|
|
Sign up to set email alerts
|

Networking Activities and Perceptions of HIV Risk Among Male Migrant Market Vendors in China

Abstract: HIV research among internal migrants in China has not fully explored the contexts and perceptions of “risk”. In 2011, urban markets in Liuzhou, China were mapped, and sixty male vendors, age 22 to 56, were selected for in-depth interviews on migration, social and family life, and perceptions and practices of sexual risk behavior. Participants were evenly divided among higher income shop and small stall vendors. All men were sexually active. Only the shop vendors reported non-marital sexual partners, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 27 publications
2
15
0
Order By: Relevance
“…Consistent with prior research, factors identified as barriers to HIV testing included misperceptions about HIV, lack of knowledge on the importance of knowing one's HIV status, lack of access to testing, and fears of deportation [24][25][26][27]. These factors have been found in other studies among vulnerable groups as barriers to HIV testing [6,[28][29][30]. Men's lack of health help-seeking behaviors has been documented in literature worldwide [31] and has been attributed to attempts at enacting masculine ideals [20].…”
Section: Discussionsupporting
confidence: 75%
“…Consistent with prior research, factors identified as barriers to HIV testing included misperceptions about HIV, lack of knowledge on the importance of knowing one's HIV status, lack of access to testing, and fears of deportation [24][25][26][27]. These factors have been found in other studies among vulnerable groups as barriers to HIV testing [6,[28][29][30]. Men's lack of health help-seeking behaviors has been documented in literature worldwide [31] and has been attributed to attempts at enacting masculine ideals [20].…”
Section: Discussionsupporting
confidence: 75%
“…As found in past research [46-48], the studies in this Special Issue found lower condom use by men and women during sex with regular partners or partners perceived as trustworthy or familiar [43, 44, 45]. In these relationships trust is conferred through interpersonal connections as well as through indirect connections - as when new sexual partners are introduced through friends or colleagues [43, 44]. By contrast, condoms are often associated with distrust, commercial sex, uncleanliness, and emotional distance.…”
Section: Future Directionssupporting
confidence: 65%
“…In China, interventions to prevent heterosexual HIV/STI transmission have largely focused on pre-defined at-risk groups – especially FSW [28, 34-37] and IDU [28, 38]. Our work, however, found high levels of self-reported risk behaviors taking place outside the context of commercial sex partnerships, including unprotected sex with non-commercial partners, multiple types of sexual partnerships, and one-time sex with casual partners [39-43]. These studies force us to rethink traditional risk profiles or behaviors and to consider the importance of sexual networks as links between individuals with “typical” high-risk behaviors and members of the general population become apparent.…”
Section: Future Directionsmentioning
confidence: 91%
See 2 more Smart Citations